2020
DOI: 10.3390/ma13132927
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Study of the Covalent Grafting of Triazole Layer onto the Gold Surface

Abstract: Finding novel strategies for surface modification is of great interest in electrochemistry and material sciences. In this study, we present a strategy for modification of a gold electrode through covalent attachment of triazole (TA) groups. Triazole groups were electrochemically grafted at the surface of the electrode by a reduction of in situ generated triazolediazonium cations. The resulting grafted surface was characterized before and after the functionalization process by different electrochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The interaction of the oxygen molecules (in vacuum and water using the conductor-like screening model) [23][24][25] with the bare and grafted gold surfaces was evaluated at different reaction sites. The results gave important molecular insight into the adsorption energy and geometry-induced changes brought about by the interaction of oxygen molecule on the grafted interface [26].…”
Section: Molecular Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of the oxygen molecules (in vacuum and water using the conductor-like screening model) [23][24][25] with the bare and grafted gold surfaces was evaluated at different reaction sites. The results gave important molecular insight into the adsorption energy and geometry-induced changes brought about by the interaction of oxygen molecule on the grafted interface [26].…”
Section: Molecular Modelingmentioning
confidence: 99%
“…Bond dissociation energy (BDE) is widely used to evaluate the stability of diazonium salt-grafted layers [25][26][27][28]. The computed BDE for the carboxyphenyl group was −52.19 kcal/mol.…”
Section: Dft Calculationmentioning
confidence: 99%
“…In the case of amines, such modifications are denoted as grafting. This process involves the formation of a covalent bond between the amino group and the electrode surface [2].…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical modification of an electrode entails a process where the el undergoes electrochemical treatments to deposit specific chemical species on its Such modifications are conducted to increase sensitivity, reduce detection limits, e selectivity, increase specificity, or enable the analysis of electrochemically compounds [1]. In the case of amines, such modifications are denoted as graftin process involves the formation of a covalent bond between the amino group electrode surface [2].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there a few studies focusing on this approach have been reported so far. 30,38,39 Particularly, as far as we are aware, on the study at the molecular level of covalent functionalization of 1,2,4-triazole derivatives onto layered material surfaces including graphene has not been addressed yet.…”
mentioning
confidence: 99%